2006
DOI: 10.1086/503871
|View full text |Cite
|
Sign up to set email alerts
|

Contact Binaries with Additional Components. I. The Extant Data

Abstract: We have attempted to establish an observational evidence for presence of distant companions which may have acquired and/or absorbed the angular momentum during evolution of multiple systems thus facilitating or enabling formation of contact binaries. In this preliminary investigation we use several techniques (some of them distance-independent) and mostly disregard detection biases of individual techniques in an attempt to establish a lower limit to the frequency of triple systems. While the whole sample of 15… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
217
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(240 citation statements)
references
References 73 publications
21
217
2
Order By: Relevance
“…Some of them are eclipsing binaries with a pulsating component, and some semi-regular variables with unknown short-term variations or some pulsating ellipsoidal variables (Derekas et al 2006;Nie, Zhang, & Jiang 2010;Faigler & Mazeh 2011;Faigler et al 2012). In several studies, V1464 Aql was classified as a spectroscopic binary system, RR Lyr (RRc), an eclipsing binary, possibly contact (EC) or semi-detached system (ESD) (Duerbeck 1997;Pourbaix et al 2004;Pribulla & Rucinski 2006; PASA, 30, e016 (2013) doi:10.1017/pasa.2012.016 Aerts et al (2002). c Henry et al (2004).…”
Section: Resultsmentioning
confidence: 99%
“…Some of them are eclipsing binaries with a pulsating component, and some semi-regular variables with unknown short-term variations or some pulsating ellipsoidal variables (Derekas et al 2006;Nie, Zhang, & Jiang 2010;Faigler & Mazeh 2011;Faigler et al 2012). In several studies, V1464 Aql was classified as a spectroscopic binary system, RR Lyr (RRc), an eclipsing binary, possibly contact (EC) or semi-detached system (ESD) (Duerbeck 1997;Pourbaix et al 2004;Pribulla & Rucinski 2006; PASA, 30, e016 (2013) doi:10.1017/pasa.2012.016 Aerts et al (2002). c Henry et al (2004).…”
Section: Resultsmentioning
confidence: 99%
“…Yang & Liu (2003) considered both mass exchange and mass loss mechanisms that could cause the observed decrease in the period but found that the cyclic variation superimposed on the decreasing trend was quasi-periodic; hence, it could only be attributed to magnetic activity. Pribulla & Rucinski (2006) and Rucinski et al (2007) did not detect the signature of a third body in their studies dedicated to detecting faint third bodies in contact binary systems. In addition, broadening functions constructed for radial velocity analysis by Pribulla et al (2009a) did not show any evidence of a third companion in the system.…”
Section: Rw Commentioning
confidence: 96%
“…Tokovinin & Smekhov (2002) have noted that periods above ∼ 10 days are rarer (relative to shorter periods) among the inner binaries of triples than in the population as a whole, and possibly this is accounted for by the combination of Kozai cycles and tidal friction (KCTF). Pribulla & Rucinski (2006) have noted that as many as 42% of contact binaries appear to be in triples (and arguably 59% in a more thoroughly examined subsample), and it could be that KCTF has contributed to this; although we probably need the additional influence of magnetic braking to drive fairly close low-mass binaries generated by KCTF to contact on a timscale of < ∼ 10 9 .…”
Section: Discussionmentioning
confidence: 96%